Legal Responsibility of Travel Services for Consumer Losses - Nainggolan, Ibrahim; Rahimah, Rahimah (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Organizing travel between the travel agency and its consumers, namely service users, has a legal relationship that creates responsibilities, rights and obligations between the parties. This human relationship in Islam is known as muamalah. One thing that people often do is an agreement. In Arabic, an agreement is 'uquud' which means a (recorded) contract agreement. Legal consequences will arise if business actors do not carry out their obligations properly and consumers will complain if the results received are not in accordance with the agreement at the time of the sale and purchase transaction that was carried out. In a contract or agreement, if the business actor can fulfill his obligations well then the business actor has made an achievement, but if the business actor has been negligent and cannot fulfill his obligations well then a default will arise. Apart from that, business actors or in this case travel agencies can also be subject to criminal penalties, Article 61 UUPK "criminal prosecution can be carried out against business actors and their management". It is also stated in Article 62 "Paragraph (1) Business actors who violate the provisions as intended in Article 8, Article 9, Article 10, Article 13 paragraph (2), Article 15, Article 17 paragraph (1) letter a, letter b, letter c, letter e, paragraph (2) and Article 18 shall be punished with a maximum imprisonment of 5 (five) years or a maximum fine of Rp. 2,000,000,000.00 (two billion rupiah). Paragraph (2) Business actors who violate the provisions as intended in Article 11, Article 12, Article 13 paragraph (1), Article 14, Article 16, and Article 17 paragraph (1) letters d and letter f shall be sentenced to imprisonment for a maximum of 2 (two) ) years or a maximum fine of IDR 500,000,000.00 (five hundred million rupiah)